Hopeless neuroma: the neurotized free flap tissue augmentation as salvage therapy ; a concept and clinical demonstration - Aman, Martin; Glaser, Julia; Böcker, Arne Hendrik; Thielen, Mirjam; Eisa, Amr; Bigdeli, Amir Khosrow; Gazyakan, Emre; Kneser, Ulrich; Harhaus-Wähner, Leila (Journal of Personalized Medicine, 2023)
Therapy-resistant neuroma pain is a devastating condition for patients and surgeons. Although various methods are described to surgically deal with neuromas, some discontinuity and stump neuroma therapies have anatomical limitations. It is widely known that a neurotizable target for axon ingrowth is beneficial for dealing with neuromas. The nerve needs “something to do”. Furthermore, sufficient soft tissue coverage plays a major role in sufficient neuroma therapy. We aimed, therefore, to demonstrate our approach for therapy of resistant neuromas with insufficient tissue coverage using free flaps, which are sensory neurotized via anatomical constant branches. The central idea is to provide a new target, a new “to do” for the painful mislead axons, as well as an augmentation of deficient soft tissues. As indication is key, we furthermore demonstrate clinical cases and common neurotizable workhorse flaps.